(untitled) (Balneo and PRM Research Journal, 2024)
Zoledronate (or zoledronic acid) represents a standard (guideline-based) approach in the area of anti-resorptive medication (namely, an annual 15-minute perfusion of 5 mg for os-teoporosis treatment), while the same drug (with doses/regimes variations) is used for other bone metabolic conditions such as Paget’s disease of the bone or skeleton metastasis originating from different cancers. The objective of this narrative review was to highlight the most recent published data with respect to zoledronic acid use as part of the complex clinical management amid primary osteoporosis in addition to other osteo-metabolic clin-ical entities. This was a research based on exploring PubMed database with respect to the search words “zoledronic acid” and “primary osteoporosis”. We included highly relevant (from the clinical perspective), English-published, full-length articles that have been re-cently published (between January 2023 and March 2024). From 249 results, 31 articles met the inclusion timeline criteria across the 15-month analysis and the final results were based on data provided from 16 articles. Important insights concern not only the zoledronic acid administration, the efficacy and the safety profile, but, also, an extension on daily indications with concern to diabetic bone disease, liver osteodystrophy, osteogen-esis imperfecta or Paget’s disease of the bone.